THE EFFECT OF CAPITAL STRUCTURE ON FIRM VALUE BY USING DIVIDEND POLICY AS AN INTERVENING VARIABLE (Study on Pharmaceutical Sub Sector Companies) - Hairudin Hairudin; Desmon Desmon (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2020)
This study aims to examine and determine the effect of capital structure on firm value, with dividend policy as an intervening variable in the pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the period 2009-2016, with a total sample of 5 companies. This study uses path analysis. The results of this study indicate that the capital structure has a negative influence on firm value. While the capital structure also has a negative influence on dividend policy and dividend policy has a positive influence on company value, from the results of path analysis it is concluded that dividend policy can mediate the relationship between capital structure and firm value.